The presidency in a separated system - Jones, Charles O. (Washington, D.C. : Brookings Institution Press, 2005)
"Examines the organizational, political, and procedural challenges faced by postwar U.S. presidents, from Truman through George W. Bush, working in a separated system of government"--Provided by publisher
Perspectives on the presidency -- Presidents and the presidency -- Organizing to govern in the separated system -- Public standing of the president -- Presidents, mandates, and agendas -- Presidents and lawmaking in a separated system -- Making laws -- Thinking about change.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Presidents -- United States -- History; Separation of powers -- United States; United States -- Politics and government; Présidents -- États-Unis -- Histoire; Séparation des pouvoirs -- États-Unis.; États-Unis -- Politique et gouvernement; POLITICAL SCIENCE -- Political Process -- Leadership; POLITICAL SCIENCE -- American Government -- General; Politics and government; Presidents; Separation of powers; United States; Presidentschap; Scheiding der machten; History